Analysis of Photosynthetic Differences of Rice Germplasm in Southeast Asia Based on Leaf-Tissue Structure, Physiology, and iTRAQ - Xiaoli Zhang; Maoyan Tang; Hui Wang; Wei Tao; Qiang Wang; Lei Chen; Guoqing Gao; Ronghua Lv; Tianfeng Liang (Agronomy, 2022)
Photosynthesis is responsible for 90–95% of organic matter in crop yield. The light energy utilization rate of high-yielding rice varieties is 1.0–1.5%, but the ideal value is about 3–5%. Yield can be further improved by improving photosynthetic function. Through the initial screening and re-screening of 220 Southeast Asian germplasm resources, we found that the net photosynthetic rate of Southeast Asian germplasm resource C1 was 36.96 μmol m−2 S−1, which is close to that of C4 plant maize and 3.26 times higher than that of Southeast Asian germplasm resource G164 at 11.26 μmol m−2 S−1. Using C1 and G164 as materials, we compared the tissue structure, chloroplast ultrastructure, photosynthetic physiological indicators, and proteomics of sword leaves to determine the factors affecting photosynthetic function. Compared with G164, C1 exhibited increased number of vascular bundles, increased stomatal size and density, more abundant and neatly arranged chloroplasts and thylakoid grana, and higher chlorophyll fluorescence parameters. The activities and contents of the key photosynthetic enzyme Rubisco were higher in C1 than in G164. The two germplasm resources were subjected to iTRAQ analysis, and the results showed that compared with C1, nine proteins were down-regulated and one protein was up-regulated and associated with photosynthetic electron transport in G164; a total of 17 differential proteins were associated with CO2 fixation, and nine were up-regulated and eight differential proteins were down-regulated in G164. The identified genes encode proteins in the photosynthesis and carbon fixation pathways, and the changes in gene expression were verified by real-time qPCR. The gene expression patterns were consistent with the protein expression patterns. The results suggest that most differential proteins are involved in electron transfer from PSII to PSI and in the CO2 fixation pathway, and increasing the levels of such proteins can effectively enhance the photosynthetic efficiency. C1 can be used as a donor material for selection of high light efficiency varieties and in-depth photosynthesis studies.